Critical thinking or common sense?. (13th August 2016) - Adams, Vicki
Abstract : Vicki Adams grew up in Vancouver, Canada, and graduated with a degree in animal science from the University of British Columbia before being accepted into vet school in Saskatchewan. Her animal science background has given her the population perspective that is so important in epidemiology and she now runs her own consulting company, Vet Epi